1999
DOI: 10.1177/135245859900500104
|View full text |Cite
|
Sign up to set email alerts
|

Acute/relapsing experimental autoimmune encephalomyelitis: Induction of long lasting, antigen-specific tolerance by syngeneic bone marrow transplantation

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an inducible autoimmune disease widely used as a model of the acute/relapsing stage of multiple sclerosis. We have previously shown that treatment of EAE-mice with high doses of cyclophosphamide (CY) (350 mg kg), followed by syngeneic bone marrow transplantation (SBMT), completely abrogates the clinical paralytic signs and even prevents the appearance of new relapses in the chronic-relapsing model of the disease. In the present study we examined whether this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 21 publications
0
21
0
2
Order By: Relevance
“…Spontaneous immune conditions in mice can be transferred by hemopoietic stem cells, which differentiate into T and B lymphocytes before the disease is manifest, leading to the hypothesis that the cause of immune diseases may lie in the hemopoietic stem cells, and that syngeneic bone marrow transplantation (in conjunction with an immunosuppressive treatment) induces a state of long-term unresponsiveness to myelin antigens presumably by a mechanism of tolerance that is antigen specific (9)(10)(11)(12)(13)(14). Among bone marrow cells, CD34 ϩ cells may be responsible for this effect directly or through their progeny, as exemplified by MS patients who received autologous CD34 ϩ cells (15).…”
mentioning
confidence: 99%
“…Spontaneous immune conditions in mice can be transferred by hemopoietic stem cells, which differentiate into T and B lymphocytes before the disease is manifest, leading to the hypothesis that the cause of immune diseases may lie in the hemopoietic stem cells, and that syngeneic bone marrow transplantation (in conjunction with an immunosuppressive treatment) induces a state of long-term unresponsiveness to myelin antigens presumably by a mechanism of tolerance that is antigen specific (9)(10)(11)(12)(13)(14). Among bone marrow cells, CD34 ϩ cells may be responsible for this effect directly or through their progeny, as exemplified by MS patients who received autologous CD34 ϩ cells (15).…”
mentioning
confidence: 99%
“…In addition, the interesting possibility was raised that the replacement of the aberrant immune system by a pristine, expectantly non-autoreactive system, generated by the hemopoietic stem cell graft, may possibly restore selftolerance [9].…”
Section: Autologous Hemopoietic Stem Cell Transplantation For Multmentioning
confidence: 99%
“…For example, experiments using this approach in murine multiple sclerosis (MS) showed control of the disease after SCT. 1,2 Earlier clinical studies indicated that long-term remissions of several autoimmune diseases could be achieved after SCT. [3][4][5] Here, we applied extensive ex vivo and in vivo T-cell depletion in combination with autologous SCT as salvage treatment for MS. Ex vivo T-cell depletion was done by preparing autografts enriched for CD34 þ hematopoietic stem cells, while in vivo T-cell depletion was accomplished by administration of antithymocyte globuline (ATG) and total body irradiation (TBI).…”
Section: Introductionmentioning
confidence: 99%